ANALISIS SISTEM INFORMASI AKUNTANSI SIKLUS PENDAPATAN (Studi Kasus Pada RSUD Dr. â€œXâ€) - Kusumadewi, Areta Widya; Adam, Helmy (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aims to describe and analyze accounting information systems revenue cycle forÂ general patients and Badan Penyelenggara Jaminan Sosial (BPJS) patient relating to the payment ofÂ Outpatient Installation, Inpatient Installation, and the Emergency Installation on RSUD Dr. â€œXâ€Â Hospital. This study is a descriptive qualitative research. This study is to explain the situation,Â analyze, and provide improved solutions to the problems that arise. Methods of data collection in thisÂ study using field research consisted of interviews, observation, and documentation. The resultsÂ showed that the accounting information system of the revenue cycle is good but still not effectivelyÂ linked to (1) advance and the money deposited while the general patient and BPJS patient, (2)Â differences in hospital rates with BPJS rates, (3) Â the incompleteness of the procedure and flow chart.Â Recommendations of these problems is to improve and update the revenues and cash receiptsÂ procedures in order to support service activities.Keywords: Accounting Information Systems, Revenue Cycle, Hospital, BPJS.